2015
DOI: 10.1140/epjc/s10052-015-3677-1
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional nonlinear magnetic AdS solutions through topological defects

Abstract: Inspired by large applications of topological defects in describing different phenomena in physics, and considering the importance of three dimensional solutions in AdS/CFT correspondence, in this paper we obtain magnetic anti-de Sitter solutions of nonlinear electromagnetic fields. We take into account three classes of nonlinear electrodynamic models; first two classes are the well-known BornInfeld like models including logarithmic and exponential forms and third class is known as the power Maxwell invariant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 120 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…The behavior of heat capacity could also represent phase transitions [78,79]. By numerical calculation, we have shown the existence of phase transition in Figs.…”
Section: B Phase Transitionmentioning
confidence: 81%
See 1 more Smart Citation
“…The behavior of heat capacity could also represent phase transitions [78,79]. By numerical calculation, we have shown the existence of phase transition in Figs.…”
Section: B Phase Transitionmentioning
confidence: 81%
“…C V : which measures the heat capacity when the heat is added to the system keeping the volume constant and C P : which is used when the heat is added at constant pressure. Heat capacities can be calculated using the standard thermodynamic relations [78,79]…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…[ 24,25 ] Although the Quevedo metric solved most of the problems of the previous metrics, it faced a problem in several specific cases. To solve its problem, a new metric has been recently introduced [ 26 ] in which the problem of additional singularities that are not consistent with any of the phase transition points is not observed.…”
Section: Extended Phase Space Phase Transition and Thermal Stabilitymentioning
confidence: 99%
“…However, Quevedo metric is not, completely, a successful model in several specific systems and its Ricci scalar has extra divergence point without physical interpretation. Finally, a new metric was proposed [ 26–28 ] in which the problem of mismatched divergency is not observed. [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…We will also analyze the non-perturbative corrections to the information-theoretical geometry of this system. This will be done using different informational theoretical metrics for this system [52][53][54][55][56][57][58]. It will be observed that these non-perturbative corrections will produce a non-trivial modification to the information-theoretical geometry of this system.…”
Section: Introductionmentioning
confidence: 99%